Students with Autism Participating in Recess - Lucas, Matthew D.; Nichols, Kourtney M. (Journal of the American Academy of Special Education Professionals, 2010)
The participation of a student with autism in recess can often be both challenging and rewarding for all students and the general education teacher. This paper will address common characteristics of students with autism and present basic solutions to improve the education of these students in the recess setting. Initially the definition, behavioral characteristics, and prevalence of autism will be presented. This will be followed by a brief discussion of autism for an individual in the classroom, and possible benefits, challenges, and solutions for children with autism in the recess setting. Lastly, specific methods of including a student with autism in a basic recess activity will be discussed.